Identification of binding domains and key amino acids involved in the interaction between BmLARK and G4 structure in the BmPOUM2 promoter in Bombyx mori. (17th August 2020) - Peng, Yuling; Niu, Kangkang; Yu, Guoxing; Zheng, Mingxi; Wei, Qiulan; Song, Qisheng; Feng, Qili
Abstract: It has been found that the non‐B form DNA structures, like G‐quadruplex (G4) and i‐motif, are involved in many important biological processes. Our previous study showed that the silkworm transcription factor BmLARK binds to the G4 structure in the promoter of the transcription factor BmPOUM2 and regulates its promoter activity. However, the binding mechanism between BmLARK and BmPOUM2 G4 structure remains unclear. In this study, binding domains and key amino acid residues involved in the interaction between BmLARK and BmPOUM2 G4 were studied. The electrophoretic mobility shift assay results indicated that the two RNA‐recognition motifs (RRM) of BmLARK are simultaneously required for the binding with the G4 structure. Either RRM1 or RRM2 alone could not bind with the G4 structure. The zinc‐finger motif was not involved in the binding. A series of mutant proteins with specific amino acid mutations were expressed and used to identify the key amino acid residues involving the interaction. The results indicated that β sheets, especially the β1 and β3 sheets, in the RRM domains of BmLARK played critical roles in the binding with the G4 structure. Several amino acid mutations of RRM1/2 in ribonucleoprotein domain 1 (RNP1) (motif in β3 strand) and RNP2 (motif in β1 strand) caused loss of binding ability, indicating that these amino acids are the key sites for the binding. All the results suggest that RRM domains, particularly their the RNP1 and RNP2 motifs, play important roles not only in RNA recognition, but also in the G4 structure binding.